Respectful maternity care and associated factors among mothers who gave birth in three hospitals of Southwest Ethiopia: A cross-sectional study - Adugna, Amanuel; Kindie, Kassa; Abebe, Gossa Fetene (Frontiers in Public Health, 2023)
Background One of the primary barriers to reducing maternal morbidity and mortality is disrespect and abuse during childbirth in biomedical facilities. Despite the serious consequences of disrespect and abuse during childbirth, there is no evidence of the prevalence of respectful maternity care in Southwest Ethiopia. This study aimed to assess the prevalence of respectful maternity care and associated factors among mothers who gave birth in three hospitals in Southwest Ethiopia. Methods An institution-based cross-sectional study was conducted among 348 mothers who gave birth in three hospitals in Southwest Ethiopia. Bivariable and multivariable binary logistic regression were used to identify the factors of respectful maternity care. Results In this study, 348 mothers with their newborns were included, making a response rate of 100%. The overall prevalence of respectful maternity care was 81.2%. Maternal age [AOR = 2.54; 95% CI (1.01–6.43)]; maternal occupation [AOR = 5.23; 95% CI (1.15–23.72)]; antenatal care follows-up [AOR = 2.86; 95% CI (1.01–8.20)]; and discussions with the provider about the place of delivery during antenatal care follow up [AOR = 5.58; 95% CI: (2.12–14.70)] were found to be the most significant components of respectful maternity care. Conclusion The provision of respectful maternity care was high, but there are complaints of disrespect and abuse still present in three hospitals in Southwest Ethiopia. Maternal age, maternal occupation, antenatal follow up, and discussion with the provider about the place of delivery during antenatal follow-up were associated with respectful maternity care. Thus, improving antenatal care service utilization and discussions with health care providers about the place of delivery during antenatal care follow-up should be focused on.